Peningkatan Range of Movement (ROM) Atlet Sepakbola Pasca Cedera Ankle dengan Terapi Massage dan Latihan Pembebanan - Andy Widhiya Bayu Utomo; Toyo Wibowo; Arief Nur Wahyudi (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Persinga Ngawi is a League 3 football club witha fairly solid match schedule,so it demands increasedathletes' physical activity. Exercise, match,and post-match are stages that must be followed by football athletes,which more or less pose a risk of injury, one of whichis an ankleinjury.Massage therapy and weight trainingcan be used to reduce ankle injuries. This study aimedto analyze the increase in Range of Movement (ROM) of Persinga Athletes after ankleinjury with massage therapy and weight training. This type of research is a pre-experimental design with a one-grouppretest-posttest design. This research was carried out in January-February 2022. The population of this study was24 athletes of Persinga U-17 football in Ngawi Regency. The sampling technique used was purposive sampling with the criteria of athletes experiencing post-ankleinjuries, so a sample of 15 athletes was obtained. The stages of the research are conducting pre-test and post-test by measuring the Range of Movement (ROM) in the anklejoint on massage therapy and loading exercises with theraband. MeasuringRange of Movement (ROM) for Persinga U-17 athletes on massage therapy and weight training showed an increase in ROM of 35% in flexion movements and 30% in extension movements.The Wilcoxon Signed-RankTest revealed a sig value of 0.043 (p0.05), indicating differences between the pre-and post-test outcomes after massage therapy and weight training. This suggests that massage therapy and weight training can help Persinga U-17 athletes in Ngawi Regency recover from ankle injuries.